Utilitarianism and the pandemic - Savulescu, Julian; Persson, Ingmar; Wilkinson, Dominic (Bioethics, 2020)
There are no egalitarians in a pandemic. The scale of the challenge for health systems and public policy means that there is an ineluctable need to prioritize the needs of the many. It is impossible to treat all citizens equally, and a failure to carefully consider the consequences of actions could lead to massive preventable loss of life. In a pandemic there is a strong ethical need to consider how to do most good overall. Utilitarianism is an influential moral theory that states that the right action is the action that is expected to produce the greatest good. It offers clear operationalizable principles. In this paper we provide a summary of how utilitarianism could inform two challenging questions that have been important in the early phase of the pandemic: (a) Triage: which patients should receive access to a ventilator if there is overwhelming demand outstripping supply? (b) Lockdown: how should countries decide when to implement stringent social restrictions, balancing preventing deaths from COVID‐19 with causing deaths and reductions in well‐being from other causes? Our aim is not to argue that utilitarianism is the only relevant ethical theory, or in favour of a purely utilitarian approach. However, clearly considering which options will do the most good overall will help societies identify and consider the necessary cost of other values. Societies may choose either to embrace or not to embrace the utilitarian course, but with a clear understanding of the values involved and the price they are willing to pay.